Plan de marketing estratégico para el posicionamiento de la cooperativa de ahorro y crédito salitre en el cantón Vinces provincia de los Ríos - Huacon Suarez, Washington Calixto (2015)
This research is part of the financial institutions and credit unions in the country try every day to attract new customers based primarily on advertising, since customers are the primary basis for their good performance in the market. Given that customers for cooperatives are essential for high levels of profitability hand so you can stay and position in the highly competitive market is the financial it is vital for cooperative members have a tool to help make decisions...